2021
DOI: 10.1177/20503121211000911
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella and Shigella and antimicrobial susceptibility profiles among adult patients with complaints of diarrhea at Hawassa comprehensive specialized hospital, Hawassa, Ethiopia

Abstract: Introduction: Diarrhea is one of the public health important diseases in developing countries. Among the causative agents of diarrhea, Salmonella serovars and Shigella species continue to play a major role in resource-limited countries. The aim of this study was to assess the prevalence of Salmonella and Shigella, risk factors, and antimicrobial susceptibility profiles among adult patients with complaints of diarrhea. Methods: A hospital-based cross-sectional study was conducted among adult patients with compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…In the current study, none of the patient-related factors were shown to have statistically significant association with detection of Salmonella from stool of diarrheic patients unlike previous studies where consumption of raw vegetables and stool being watery [26], and poor hand washing practices and consumption of raw/uncooked foods were associated with detection of Salmonella in diarrheic patients [28]. The reason why we did not observe such association in this study could be due to small sample size and better practices of cleaning raw vegetables before consumption among study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, none of the patient-related factors were shown to have statistically significant association with detection of Salmonella from stool of diarrheic patients unlike previous studies where consumption of raw vegetables and stool being watery [26], and poor hand washing practices and consumption of raw/uncooked foods were associated with detection of Salmonella in diarrheic patients [28]. The reason why we did not observe such association in this study could be due to small sample size and better practices of cleaning raw vegetables before consumption among study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…This result corroborates those of Tural et al 2015 [11]. A slight decrease in prevalence rate was reported by Yesigat T et al [15], who reported 4.1% and this differs from Kassahun Abera et al [16]. On the other hand, Kuma Diriba et al [17] reported a percentage of 8.6% and 12% of the overall prevalence of Salmonella and Shigella species.…”
Section: Prevalence and Associated Risk Factors For Salmonella Spp An...supporting
confidence: 87%
“…is high in resource-limited countries. 5,48 Thus, our study might suggests the need for strong control strategies of the pathogens in urban equally as in rural settings in countries like Ethiopia.…”
Section: Discussionmentioning
confidence: 85%